PERANAN IMM DALAM EKSISTENSI LITERASI DAKWAH DI ERA DIGITAL - Ridwan, Siti Fatimah; Sahar, Muh. Faisal; M, Nurhikmah; Madjid, Andi Nurkholis (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2022)
In this all-digital era, where it is easier for us to access information with a wider range, it should be used as best we can to develop various aspects, one of which is da'wah literacy. In addition to being a driving force for advancing da'wah literacy, digital sophistication can also be a boomerang that actually makes Islamic da'wah literacy fall behind if it is not used properly and correctly. Research and Scientific Development Sector (RPK) The Leader of the Ibnu Taimiyah Commissariat FAI UM Parepare took the initiative to deepen research on the existence of da'wah literacy in the digital era whose object is the Muhammadiyah Student Association (IMM) and its role in advancing da'wah literacy